The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1061/jswbay.0000917
|View full text |Cite
|
Sign up to set email alerts
|

Geospatial Modeling Suggests Threats from Stormy Seas to Rhode Island’s Coastal Septic Systems

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Human fecal contamination has been associated with the density of septic tanks in a watershed, and septic systems have been linked to gastrointestinal illness in children and chronic exposure to Cryptosporidium in regions where well water is a primary source of drinking water. Climate change may also alter the contribution of septic systems to pollution, irrespective of system age, especially in coastal communities where sea-level rise may increase the frequency and intensity of wave inundation and storm surges that flood OWTS. , Research has also demonstrated that storm events can influence septic function and the flow of septic-derived pollutants into surface water. , Septic density may also be a factor defining the contribution of septic systems to pollution loads; yet, our ability to predict how environmental conditions (e.g., soil type, weather conditions, climate) interact with septic density to influence the pollution load from onsite systems is still limited …”
Section: Discussionmentioning
confidence: 99%
“…Human fecal contamination has been associated with the density of septic tanks in a watershed, and septic systems have been linked to gastrointestinal illness in children and chronic exposure to Cryptosporidium in regions where well water is a primary source of drinking water. Climate change may also alter the contribution of septic systems to pollution, irrespective of system age, especially in coastal communities where sea-level rise may increase the frequency and intensity of wave inundation and storm surges that flood OWTS. , Research has also demonstrated that storm events can influence septic function and the flow of septic-derived pollutants into surface water. , Septic density may also be a factor defining the contribution of septic systems to pollution loads; yet, our ability to predict how environmental conditions (e.g., soil type, weather conditions, climate) interact with septic density to influence the pollution load from onsite systems is still limited …”
Section: Discussionmentioning
confidence: 99%
“…Regarding the challenges and risks for coastal infrastructure generated by CC, the sphere that has received the most attention is the analysis of the potential adverse effects of sea level rise on coastal areas and their infrastructure 85 . This scenario may pose risks for the industrial sector and private households 86 . Against this background, several studies provide evidence of the relevance of adaptation measures combining technology and community training and nature-based solutions to increase resilience and reduce vulnerability in coastal areas 87 .…”
Section: Resultsmentioning
confidence: 99%
“…Elevation of groundwater further diminishes the vertical space required for treatment (Cox et al 2019(Cox et al , 2020. For example, viruses in wastewater are often neutralized when the viral outer protein coat is absorbed by the surfaces of unsaturated soil grains, degrading or deactivating those viruses.…”
Section: On-site Sewage Disposalmentioning
confidence: 99%